Exploring Students’ English Autonomy Using Mobile Application At The Time Of The Pandemic - Pradittya, Rindie; Ridwan, Iwan (Peneliti.net, 2024)
While the impact of the COVID-19 pandemic on education has been widely discussed, there is little empirical evidence for student independence experiences. This study explores and collects information about the experiences students have while learning English online, their perceptions, and how their experiences shape their potential for autonomous learning. The current study uses a Narrative qualitative approach. Data was collected through an online form questionnaire, which was administered to 20 students in grades 11 and 12 of Vocational High School in Karawang. The purpose of this study is to review the use of English learning applications in increasing student autonomy and also students' perspectives in using these applications during online learning. The results showed that students participating in this study appeared to have a fairly good online English learning experience. It was highlighted that students' online learning experiences, in some ways, influenced their self-assessment potential for independent learning. They receive a variety of learning instructions and engage in various types of language learning activities. The majority of students find learning English online quite enjoyable, but many of them show considerable potential to act as independent learners.